FEATURES OF THE ALBANIAN TOTALITARIAN STATE RELATIONS BETWEEN RELIGION AND THE STATE - Sokol Paja (European Scientific Journal, ESJ, 2014)
After the end of World War II, it was established the totalitarian regime. Albania was transformed into the country where the most severe and intolerant form of Communism originated and developed from, and which isolated the country from the outer world and put it in a state siege. Years went by and every power was concentrated in the hand of one single man, The Dictator Enver Hoxha. the totalitarianism that was being established in Albania, considered all as being equal and aimed at having the whole nation under its control. In this paper I will present the features of the Albanian totalitarian state during 1945-1990. I will introduce the way the state was organized, how the leadership of that time, headed by the state chairman Enver Hoxha, managed to run the state. how did such a system manage to change, transform the whole social life and why was Religion exactly impinged? I will focus on the aspect of human freedoms and rights such as: practice of religious freedoms, imprisonings, murders of the clergymen, and why was the state interested in invading the Clergy. What was the real reason of religion prohibition?